Trilobites from Vargas Peña (Llandovery) of Itaugúa, eastern Paraguay : advances in trolobites research - Tortello, Franco (2008)
Fil: Tortello, Franco. División Paleontología Invertebrados, Museo de La Plata, Paseo del Bosque s/n, 1900 La Plata, Argentina